FRI0156 Adalimumab treatment is associated with decreased concomitant RA medication use over 24 months. (23rd January 2014) - Furst, D.E.; Mozaffarian, N.; Grant, S.; Cifaldi, M.; Clewell, J.; Kremer, J.; Shaw, J.W.
Abstract : Background: Adalimumab (ADA) is an effective medication in the treatment of rheumatoid arthritis (RA). However, it is not clear whether the use of ADA is associated with altered use of concomitant RA medications. Objectives: To examine changes in concomitant RA medications after initiation of ADA. Methods: The CORRONA registry is a multicenter, longitudinal rheumatology database (for physical examination data, laboratory tests, and patient outcomes) from more than 90 academic and private sites across the USA. We examined RA patients enrolled in CORRONA between March 2002-September 2011 who initiated ADA and had at least one follow-up visit. RA-related concomitant medications (methotrexate (MTX), prednisone, NSAIDs, intra-articular joint injections (IA)), anti-depressant use, comorbidities (HBP, CVD, lymphoma, other cancers, liver disorders, asthma, COPD, DM, psoriasis), and demographics (age, sex, disease duration, insurance) were examined. The trend in medication use over time was estimated using a logistic regression model with a random effect for subject, adjusting for sex, age and number of comorbodities at initiation, and use of ADA at each timepoint. The analysis includes all patients with follow-up 6, 12, 18, or 24 months after adalimumab initiation. Results: Of 1173 patients initiating ADA, available follow-up decreased over time to 417 patients by 24 months, as expected. Patient characteristics (mean ± SD): age 54.2 (12.3) years; female 79.3%; disease duration: 10.1 (9.2) years. Baseline medication usage: MTX: 67%; prednisone: 30%; NSAIDs: 61%; previous IA: 8%; antidepressants: 30%. Multivariate trend analysis over 24 months showed that both MTX and prednisone use decreased with continued ADA treatment (see table). With patients with 2 or more comorbidities, MTX use decreased and antidepressant use increased. The number of comorbidities did not affect prednisone, NSAIDs or IA usage. Conclusions: ADA use was associated with decreased MTX and prednisone use over 24 months suggesting clinical efficacy of ADA in RA disease control, across a medically diverse patient population. Disclosure of Interest: D. Furst Grant/Research support from: Abbott, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: Abbott, Actelion, Amgen, BMS, Biogen Idec, Janssen, CORRONA, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers Bureau: Abbott, Actelion, UCB (CME only), N. Mozaffarian Shareholder of: Abbott, Employee of: Abbott, S. Grant: None Declared, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott, J. Clewell Shareholder of: Abbott, Employee of: Abbott, J. Kremer Shareholder of: CORRONA, Grant/Research support from: Abbott, Amgen, AstraZeneca, BMS, Genentech, Lilly, Pfizer, Consultant for: Amgen, Genentech, Lilly, Pfizer, Employee of: CORRONA, Speakers Bureau: Abbott, Amgen, BMS, Pfizer, J. Shaw Shareholder of: Abbott, Employee of: Abbott